2016
DOI: 10.1002/aoc.3497
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure of a new ternary monocopper(II) complex containing mixed ligands of 2,2′‐diamino‐4,4′‐bithiazole and picrate:in vitroanticancer activity, molecular docking and reactivity towards DNA

Abstract: A new ternary monocopper(II) complex with co-ligands of 2,2′-diamino-4,4′-bithiazole (dabt) and picrate (pic), namely [Cu(dabt)(pic) 2 ], has been synthesized and characterized using elemental analyses, molar conductance measurements, infrared and electronic spectral studies and single-crystal X-ray diffraction. The crystal structure analyses revealed that the copper(II) ion has a {CuN 2 O 4 } distorted octahedral coordination environment. The hydrogen bonding interactions contribute to a three-dimensional sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The binding ability of complexes to DNA is investigated through molecular docking procedures. Here, the E2 regulatory protein binding DNA targets (PDB ID: 423D) are considered for the calculations [ 80 , 81 ]. The regulatory signals of the virus are dependent on the nucleotides that are involved in protein binding along with the deformation ability of the corresponding target DNA region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding ability of complexes to DNA is investigated through molecular docking procedures. Here, the E2 regulatory protein binding DNA targets (PDB ID: 423D) are considered for the calculations [ 80 , 81 ]. The regulatory signals of the virus are dependent on the nucleotides that are involved in protein binding along with the deformation ability of the corresponding target DNA region.…”
Section: Resultsmentioning
confidence: 99%
“…It can also be observed that complex 1 forms three explicit hydrogen bonds with DG7, DA17, and DG19 residues, while complex 2 has only one hydrogen bond with DC18 residue which could be the reason for the stronger interaction observed in the case of complex 1 over complex 2. e binding ability of complexes to DNA is investigated through molecular docking procedures. Here, the E2 regulatory protein binding DNA targets (PDB ID: 423D) are considered for the calculations [80,81].…”
Section: Molecular Docking Studies On Metal Complexes Binding To E2mentioning
confidence: 99%